Augmented reality application for dissemination of cultural heritage [Aplicación en realidad aumentada para divulgación del patrimonio cultural] (2016)
This article brings together the methodological processes, from the technical and the visual, for the design an application in augmented reality (AR), focused on the awareness of the importance of the architectural heritage of the city of Medellin, in the context of the Colciencias call N. 570 for Art and Culture. General objective: To design and implement an application with augmented reality content for the reactivation of the Cisneros Marketplace. Specific objectives: (I) To characterize the architectural elements susceptible to be applied under augmented reality; (II) to propose a scenario of experience between technology, heritage and citizenship; (III) to design the graphic proposal and the generation of digital contents. Methodology: Quantitative and qualitative. The following research moments were created in order to collect the data: (I) Raising of a state of the art on the subject; (II) identifying planimetry and recreation resources of the city in order to visually reconstruct the building; (III) development of 2D and 3D prototypes for the digital space realization; (IV) refinement of content and data that will accompany the experience; and (V) testing with the different technological structures that will allow to generate the final model in augmented reality for mobile applications. Results: Experimental tests were performed with different audiences, ranging from 21 to 46 years of age. Because the application was developed and evaluated only for devices with Android operating system, in situ tests were organized in the physical area where the Marketplace was located. Conclusions: The possibilities offered by augmented reality in heritage sites have grown exponentially in recent years due to its great appeal to the public, constituting an important resource within the most avant-garde cultural programs. For this project, it is an opportunity for expansion and to make known this technology in the city and country.